Correlation of cytomorphology with flowcytometric immunophenotyping in patients of acute leukemia in tertiary care hospital - Garima Pandey; Rahsmi Nichlani; Farah Jalaly; Naila Durrani; Manal Ashraf Ali (Journal of Pathology of Nepal)
Background: Morphological diagnosis of leukemias may sometimes not correlate with flow cytometry diagnosis. Classification of hematological neoplasm by the World Health Organization gives priority to cytogenetic, molecular biology, and even patient history, in an attempt to classify patients primarily regarding prognosis. Cytomorphology and immunophenotyping complement each other. Morphology is burdened by a high degree of subjectivity. That is why correlation of information provided by the two techniques is still absolutely necessary. The aim of our study was to correlate between cytomorphological findings and immunophenotyping results on a group of patients investigated for acute leukemia.